Sequential injection analysis for the determination of fluoroquinolone antibacterial drug residues by using eosin Y as complexing agent - Kanokwan Chaiyasing (2018)
© 2018 Elsevier B.V. A sequential injection analysis (SIA) method was developed for the rapid and sensitive determination of fluoroquinolone residues, including norfloxacin, ciprofloxacin and enrofloxacin, in fish samples. The method is based on the reaction between fluoroquinolone drug and eosin Y in Britton-Robinson buffer (pH 2.0), forming pink colored complexs with maximum absorptions at 522, 525 and 527 nm for norfloxacin, ciprofloxacin and enrofloxacin, respectively. Linearity ranges were found to be 0.05–10.0 mg L−1(r2= 0.9996), 0.1–10.0 mg L−1(r2= 0.9995) and 0.05–10.0 mg L−1(r2= 0.9997) for norfloxacin, ciprofloxacin and enrofloxacin, respectively. The detection limit was found to be in the range of 0.013–0.019 mg L−1. The method was tested and validated for various parameters according to main guidelines. The proposed SIA method was successfully applied for the determination of fluoroquinolone drug residues in fish samples with the sampling rate of 47 h−1. The results demonstrated that the method is accurate, precise and reproducible, while being simple, rapid, economical and less time consuming. It can be suitably applied for the estimation of fluoroquinolone drug residues in routine quality control.